#### Answer

See the picture below.

#### Work Step by Step

By calculating a few pairs, plotting each ordered pair, and connecting the dots on the graph with a smooth curve, we graph the function.
By the laws of exponents: $a^{-x}= (\frac{1}{a})^{x}$.
We transform the function to $f(x)=(\frac{1}{10})^{x}$ because it's easier to calculate with this form.
A few pairs:
$f(-1)=(\frac{1}{10})^{-1}=10$
$f(0)=(\frac{1}{10})^0=1$
$f(1)=(\frac{1}{10})^1=\frac{1}{10}$
$f(2)=(\frac{1}{10})^{2}=\frac{1}{100}$